"Why Fiction is Better than Reality": The Influence of Reading Fiction Narrative on Empathy ["Why Fiction is Better than Reality": Pengaruh Membaca Fiction Narrative terhadap Empati" - Irwanto, Katherine Amadea; Aditomo, Anindito; Natalya, Lina (ANIMA Indonesian Psychological Journal, 2020)
The fictional narrative is a form of literature often found in everyday life, such as in novels or short stories, comic strips in newspapers, and in poetry. Reading fictional literature has a positive effect, however previous research had not as yet shown any conclusive evidence that such reading increases empathy. This research was aimed at testing the influence of reading fictional narratives on empathy, mediated by narrative engagement. The method used in the research was an experimental one, with a pre-test/post-test control group design. 194 undergraduate students were actively involved as the research participants. The results of the analysis of data, using a Wilcoxon signed-rank test and a causal step approach indicated that reading a fictional narrative may significantly increase the empathy of the reader, and that the relationship of these two variables were partially mediated by narrative engagement. This research provided supportive data to the idea that fictional narratives may raise levels of empathy and that that influence is mediated by the variable of narrative engagement. The public is enjoined to read fictional narratives, such as novels, comics, short stories and poetry of a variety of genres, to experience an increase in empathy. Fiction narrative merupakan jenis bacaan yang sering ditemui dalam kehidupan sehari-hari, seperti buku novel atau cerita pendek, komik panel di surat kabar, maupun puisi. Membaca bacaan fiktif membawa dampak positif, akan tetapi penelitian terdahulu belum menunjukkan bukti yang konklusif bahwa membaca bacaan fiktif meningkatkan kemampuan empati. Penelitian ini bertujuan untuk menguji pengaruh membaca fiction narrative terhadap empati dengan dimediasi oleh narrative engagement. Metode yang digunakan dalam penelitian ini adalah eksperimen dengan pretest-posttest control group design. Terdapat 194 orang mahasiswa S1 aktif terlibat sebagai partisipan penelitian ini. Hasil analisis data dengan Wilcoxon signed-rank test dan causal step approach menunjukkan bahwa membaca fiction narrative dapat meningkatkan empati pembacanya secara signifikan, serta hubungan kedua variabel tersebut dimediasi secara parsial oleh narrative engagement. Penelitian ini menjadi dukungan data bahwa fiction narrative dapat meningkatkan empati serta pengaruh tersebut dimediasi variabel narrative engagement. Masyarakat disarankan untuk membaca bacaan fiction narrative seperti novel, komik, cerita pendek, maupun puisi dari berbagai genre agar mengalami peningkatan empati.